Effect of monoethanolamine loading on the physicochemical properties of amine-functionalized Si-MCM-41 - Anita Ramli; Sohail Ahmed; Suzana Yusup (Universiti Kebangsaan Malaysia, 2014)
Siliceous mesoporous molecular sieve (Si-MCM-41) material with highly ordered hexagonal pore arrangement was synthesized at 373 K for 8-days duration by hydrothermal method, dried at 393 K and calcined at 823 K in N2 atmosphere. The calcined Si-MCM-41 was later functionalized with 10-50 wt. % monoethanolamine (MEA) by impregnation method and dried in vacuum at 343 K. The MEA-Si-MCM-41 samples were characterized for their physicochemical properties with FTIR, XRD, TGA, HRTEM, FESEM, BET and elemental analysis. XRD results showed that the intensity of the characteristic peaks of Si-MCM-41 reduces with increasing loading of MEA indicating that the MEA molecules are loaded in the pores as well as on the surface of Si-MCM-41. The appearance of FTIR peaks corresponding to N-H, C-N and C-H bonds suggested that Si-MCM-41 has been functionalized with MEA. The presence of Si-O-Si peaks in FTIR spectra of MEA-Si-MCM-41 samples indicates that the hexagonal pore arrangement remains intact and this is supported by HRTEM images. FESEM images show that MEA-Si-MCM-41 samples became agglomerated with increase loading of MEA. TGA analyses show that the MEA-Si-MCM-41 samples are thermally stable up to 528 K. N2 adsorption-desorption isotherms show that the textural properties of Si-MCM-41 material slowly change from a mesoporous material to non-porous material as the MEA loading increases due to pore filling effect during functionalization with MEA. Detection of N, C and H by elemental analysis confirms the presence of MEA in MEA-Si-MCM-41 samples.